Postural stability during long duration quiet standing in post stroke hemiplegia. (January 2018) - Pilkar, Rakesh; Arzouni, Nibal; Nolan, Karen J.
Highlights: Quiet Standing with longer durations are important in studying balance post stroke. Significant differences in COP measures are mostly restricted to the AP direction. Phase plane stability indices significantly separate paretic and non-paretic limbs. The controlling non-paretic side may be weight overloaded during quiet standing. ML switching strategy may be employed for long duration QS to maintain balance. Abstract: Background: Inter-limb center of pressure changes and stance asymmetry in individuals with hemiplegia secondary to stroke have previously been reported for short duration quiet standing (QS). The purpose of this investigation was to assess COP displacement, velocity, and loading forces during long duration (120 s) quiet standing. The investigation also aimed at performing an inter-limb stability assessment using COP distance and velocity dependent phase plane analysis during 120 s of quiet standing in healthy controls and individuals with hemiplegia post stroke. Methods: Healthy adults (n = 12 control subjects) and individuals with hemiplegia secondary to stroke (n = 10) stood on a level floor with eyes open for 120 s while plantar pressure data was collected bilaterally. Main outcome variables included COP displacement, COP velocity, stability indices based on COP displacement and velocity variations, and the Berg Balance Assessment. In the stroke group, paired t -tests were used to perform inter-limb comparisons of the main COP outcome measures. Secondary analysis evaluated the inter-limb symmetry ratios for both groups, and independent sample t- tests were conducted to compare inter-limb ratios of COP, stability indices measures, and Berg Balance Assessment Scores between the two groups. Results: In the stroke group, COP range, COP mean velocity, COP peak velocity, and stability indices were significantly asymmetrical and greater on non-paretic side in anterior-posterior (AP) direction. Individuals with stroke demonstrated symmetrical loading forces, COP range, RMS COP, COP velocity medial-lateral (ML) ratios and this was not significantly different from the healthy controls. Conclusion: The majority of the weight bearing was imposed on the non-paretic side during 120 s of QS. As being the major contributor in maintaining balance, the non-paretic side may be over-utilized which may further lead to greater COP displacements, velocities, and potentially postural instability in AP direction. Such asymmetry in AP direction resulted in a compensatory weight "switching" strategy in ML direction.